Aluminum alloy flux-cored wire suitable for electric arc fuse additive manufacturing and preparation method and application of aluminum alloy flux-cored wire
By developing aluminum alloy flux core wire materials suitable for arc fuse additive manufacturing in 5-series aluminum alloys, the flux core wire materials composed of high-purity Mg wires and specific powders are used to solve the problem of insufficient strength in high-performance applications of 5-series aluminum alloys, and the high strength and good comprehensive performance of the material are achieved.
Patent Information
- Application Number
- CN202411788137.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The 5-Series aluminum alloy has a low strength in arc fuse additive manufacturing, which limits its application in high-performance fields. It may cause residual stress and dimensional deformation during the additive manufacturing process, reducing corrosion resistance.
An aluminum alloy core wire material suitable for arc fuse additive manufacturing was developed. By accurately adjusting the alloy composition and optimizing the fuse preparation process, a core wire material composed of high-purity Mg wire and specific powder is used to achieve uniform distribution and high strength of the alloy.
It significantly improves the tensile strength and yield strength of the material, reaches the level of high-strength aluminum alloy, enhances the comprehensive performance of the material, and is suitable for high-performance fields such as aerospace.
Smart Images

Figure CN119589195A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing and a preparation method and application thereof, and in particular to a low-cost flux-cored wire with high Mg and Zr content for arc fuse additive manufacturing and a preparation method thereof, an arc additive process and application thereof, belonging to the technical field of metal materials. Background Art
[0002] 5 series aluminum alloy is a type of aluminum alloy with magnesium as the main alloying element, which has excellent plasticity, good corrosion resistance and low yield strength. Compared with other aluminum alloy systems, a major advantage of 5 series aluminum alloy is that it can obtain stable mechanical properties without heat treatment, which greatly simplifies the production process and reduces manufacturing costs, especially in the manufacture of complex structural parts. Therefore, 5 series aluminum alloy is widely used in the fields of shipbuilding, transportation, pressure vessels, etc. These applications have high requirements for the ductility and corrosion resistance of the material, and pay more attention to the simplification of the manufacturing process and the improvement of production efficiency.
[0003] WAAM (Wire Arc Additive Manufacturing) is an advanced manufacturing process that uses an electric arc to heat a metal wire and deposit it layer by layer to build parts. It has high material utilization and manufacturing efficiency. For 5-series aluminum alloys, the application of WAAM technology has significant advantages, especially its feature of not requiring aging heat treatment, which allows the additive manufacturing process to avoid subsequent complex heat treatment steps, thereby simplifying the process, shortening the production cycle and improving the dimensional accuracy of parts. Compared with aluminum alloy systems that require heat treatment, 5-series aluminum alloys avoid problems such as part deformation, stress concentration and even cracking caused by high-temperature heat treatment and quenching during the additive manufacturing process, improving manufacturing efficiency and part geometric accuracy.
[0004] In addition, the 5-series aluminum alloy will not form low-melting eutectic compounds on the grain boundaries during the solidification process. This feature effectively inhibits the formation of pores, reduces defects in the material, and makes the additively manufactured parts have higher density and better mechanical properties. However, although the 5-series aluminum alloy has good ductility and corrosion resistance, its low yield strength (110-140MPa) limits its application in fields with high material performance requirements (≥300MPa). Especially in fields such as aerospace and high-end automobile manufacturing that have strict requirements on the comprehensive mechanical properties and high strength of materials, the strength of the 5-series aluminum alloy is relatively low and cannot fully meet the needs of these industries for high-performance materials. Therefore, the applicability of the 5-series aluminum alloy in such applications is subject to certain restrictions.
[0005] In arc fuse additive manufacturing, although the 5-series aluminum alloy does not require complex heat treatment, which simplifies the process, its low strength is still a bottleneck when it is used in parts with high strength requirements. In addition, the rapid heating and cooling during the additive manufacturing process may cause residual stress and dimensional deformation problems, and high temperature operating conditions will also lead to the formation of an oxide layer on the surface of the material, further reducing its corrosion resistance. In response to these problems, it is still necessary to optimize the alloy composition and additive manufacturing process of the 5-series aluminum alloy, aiming to improve the comprehensive performance of the material, especially its strength performance, so as to expand its application range in high-performance demand areas.
[0006] In response to the problem of low strength of 5 series aluminum alloy, we have developed a high-strength 5 series aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing process. By precisely adjusting the alloy composition and optimizing the fuse preparation process, the alloy can obtain significantly improved mechanical properties during the additive manufacturing process without relying on complex heat treatment procedures, only through homogenization or natural aging treatment, especially a good balance between strength and ductility. This innovative alloy design effectively solves the problem of low strength of traditional 5 series aluminum alloy, which limits its application in high-performance fields. This material not only maintains the original excellent plasticity and corrosion resistance of 5 series aluminum alloy, but also has higher tensile strength and yield strength. Summary of the invention
[0007] In view of the problems currently faced by 5 series aluminum alloys for arc fuse additive manufacturing, such as low strength, poor forming accuracy, easy cracking, etc., the present invention provides an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing.
[0008] At the same time, the present invention provides a preparation method of aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing. Through the method, an aluminum alloy wire with stable composition and smooth and clean wire surface can be prepared. In a single-pass multi-layer additive process, the arc light is stable without obvious splashing, the deposited layer is smooth without wavy fluctuations, the single-layer deposited layer is highly stable (0.79-0.81mm), the height difference between the sample after deposition of the additive path without secondary correction and the three-dimensional model does not exceed 2%, the surface of the deposited layer is bright without obvious oxidation inclusions, the grain size is significantly refined (<10μm), and the grain size of the commercial 5083 wire additive sample is reduced by more than 90%, the deposited state mechanical properties are excellent, and after simple homogenization treatment, the mechanical properties of the alloy are further improved (tensile strength>400MPa), reaching the level of high-strength aluminum alloy, which can be successfully applied to demanding fields such as aerospace, and finally prepare aluminum alloy samples with higher strength.
[0009] At the same time, the present invention provides an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing for use in demanding, high-performance fields such as aerospace, high-end automobile manufacturing, etc.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0011] In order to achieve the above invention objectives, the present invention adopts the following processing method to prepare aluminum alloy wire for arc additive manufacturing:
[0012] An Al-Mg-Zr cored powder flux-cored welding wire that can be used for arc additive high-strength aluminum alloy workpieces, and a corresponding low-cost manufacturing method, wherein the wire prepared by the method has the characteristics of uniform composition, small powder coating ratio, smooth wire surface, not easy to leak powder, less gas inclusions, etc. The sample of the wire printed by the arc additive process has the characteristics of high surface quality, small grain size, uniform distribution of solute atoms, small and dispersed precipitate phase size, significantly controlled solidification hot cracking, and high mechanical properties after arc deposition.
[0013] In order to achieve the above-mentioned object of the invention, the present invention adopts the following processing method:
[0014] A low-cost aluminum alloy flux-cored wire that can be used for arc additive manufacturing of high-strength aluminum alloy parts.
[0015] The present invention uses O-state 1060 pure aluminum as the coating, and uses high-purity Mg wire, ZrH2, hexafluorozirconate powder, etc. as alloy element additives. Thanks to the use of Mg wire, the amount of powder coating is significantly reduced compared to the traditional core wire processing process. At the same time, the powder is used to fill the gap between the Mg wire and the coating, further reducing the risk of gas inclusions, effectively improving the moisture-proof and antioxidant properties of the core, and there are no macroscopic pores in the additive sample (the H element content of the sample after additive is less than 12mL / 100g, and the O element content is less than 17mL / 100g, which is lower than the imported wire additive sample). The coating uses O-state aluminum with a width of 7-10mm and a thickness of 0.5-1.0mm. After cleaning the surface oxide layer and oil stains with a scraper, high-purity Mg wire with a diameter of 0.7-1.5mm and mixed powder are added according to the design composition. The mass of the powder accounts for 3-4% of the total mass of the core wire. The powder composition includes the following components in percentage by mass: 50-80% of zirconium hydride (ZrH2), 10-20% of zirconium carbide, 5-30% of hexafluorozirconate and 5-20% of potassium fluoroaluminate (KAlF4).
[0016] Furthermore, the particle size of zirconium carbide is less than 50 nm, and zirconium hydride, hexafluorozirconate and potassium fluoroaluminate are vacuum ball-milled to a particle size of 30-50 μm.
[0017] The proportion of each component is optimized and matched according to the coating size and designed wire composition to ensure the stability and excellence of the final wire performance.
[0018] Furthermore, a scraper is used to mechanically scrape the surface of the aluminum strip to clean the oxide layer and oil stains to prevent surface impurities from affecting the performance of the wire.
[0019] Furthermore, the surface of the aluminum strip is wiped and cleaned with anhydrous ethanol or acetone to ensure that the surface of the coating is clean and free of residual substances. The cleaned aluminum strip is placed in a drying oven and dried at 80-100°C for at least 1 hour.
[0020] Furthermore, professional flux-cored wire forming equipment is used, including aluminum strip forming machine, filler conveyor and wire rolling equipment. The processed aluminum strip is bent into a "U"-shaped groove through a roller forming machine for coating the core material.
[0021] Furthermore, the high-purity Mg wire and the aluminum strip are clamped at the top to ensure synchronous wire feeding of the Mg wire and the aluminum strip, and then passed through the wire rolling machine, and filled with premixed powder according to the formula ratio using a filling material conveyor between the roller forming machine and the wire rolling machine. The powder is evenly filled into the "U"-shaped groove through a quantitative feeding device, and the powder filling ratio is controlled at 3-4% of the total mass of the core wire.
[0022] Furthermore, the aluminum strip is completely covered by a forming device, and the covered seam parts are tightly joined by rolling to prevent gas penetration.
[0023] Furthermore, the coated aluminum strip is fed into a rolling mill and initially rolled into a round wire with a diameter of about 2-3 mm. During the rolling process, low speed (aluminum strip feeding speed 15-25 m / min) and high pressure (700-1200 N / mm) rolling are adopted to avoid powder scattering or core material deviation.
[0024] Furthermore, the rolled wire is placed in a vacuum annealing furnace and kept at a temperature of 300-350° C. for 30-60 minutes to eliminate rolling stress and improve the toughness of the wire.
[0025] Furthermore, the annealed wire is passed through a continuous drawing device to gradually reduce the wire diameter to 1.2-1.6 mm. The diameter reduction after each drawing is controlled at 10%-20% to avoid cracking of the coating or leakage of powder.
[0026] Furthermore, the surface of the wire is smoothed by precision polishing equipment to ensure that there are no oxides, scratches or defects on the surface of the wire. The wire is rolled into a roll according to the specified length, ensuring that the tightness is appropriate to avoid deformation during transportation and storage, and vacuum coated at the same time.
[0027] Through the above processing flow, the cored wire prepared by the present invention has the characteristics of uniform composition, smooth surface and few impurities, is suitable for high-precision and high-performance arc additive manufacturing process, and can significantly improve the mechanical properties and surface quality of deposited samples.
[0028] The functions of the components in the core wire used in the present invention are as follows:
[0029] Mg wire: It is used to provide the main alloy element Mg in the composition design, which plays a role in solid solution strengthening. Compared with the traditional process of coating Mg powder with core wire, the volume of powder can be significantly reduced, making the coating more compact and avoiding oxidation and powder leakage.
[0030] Zirconium hydride: Utilize the fine grain strengthening and precipitation strengthening effects of the Zr element during arc deposition.
[0031] Zirconium carbide: Using high melting point nano-scale zirconium carbide particles (less than 50nm, preferably 40nm) as heterogeneous nucleation in the arc deposition molten pool process, as a heterogeneous nucleation source of Al3Zr, Al3Zr is promoted to crystallize and coarsen rapidly in the high temperature molten pool. Subsequently, during the cooling process from 1027K to 912K, α-Al is promoted to nucleate on the Al3Zr surface and effectively refine the grains.
[0032] Hexafluorozirconate: Decomposition of hexafluorozirconate (one or more of sodium hexafluorozirconate, potassium hexafluorozirconate, and lithium hexafluorozirconate) is used to increase the Zr content. The generated fluoride promotes slag separation, reduces the surface tension of the melt, and promotes the polymerization, floating, and release of H2.
[0033] Potassium fluoroaluminate: It works synergistically with zirconium hydride, zirconium carbide, and hexafluorozirconate to reduce the surface tension of the melt, improve the interlayer wettability of the deposited layer, reduce hydrogen and other impurity gases in the molten pool, and reduce the pore content.
[0034] The preparation method of the high-strength aluminum alloy arc fuse additive in the present invention is:
[0035] S01, Arc Additive Manufacturing:
[0036] Aluminum substrate was used as the deposition substrate, which was fixed on the positioner workbench after cleaning and drying. ABB six-axis robot and Fronius servo power supply were used, and the following welding parameters were set: current: 65A, voltage automatic matching, welding gun moving speed: 24mm / s, shielding gas was pure Ar, flow rate 25L / min;
[0037] S02, Additive Post-Processing:
[0038] The additive material was homogenized at 420°C for 12 hours and then slowly cooled to room temperature to obtain a high-strength aluminum alloy arc fuse additive material.
[0039] The high-strength aluminum alloy arc fuse additive has a transverse tensile strength of 428-457MPa, a transverse yield strength of 294-325MPa, a transverse elongation at break of 19.4-22.5%, a longitudinal tensile strength of 424-462MPa, a longitudinal yield strength of 285-313MPa, and a longitudinal elongation at break of 16.7-21.6%.
[0040] High-strength aluminum alloy arc fuse additive is used in the demanding and high-performance fields of aerospace and high-end automobile manufacturing.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention develops an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing and a preparation method and application thereof. Compared with the traditional aluminum alloy system, it has the following advantages:
[0043] The aluminum alloy wire prepared by the present invention has the characteristics of uniform distribution of alloy elements and smooth and clean wire surface.
[0044] The sample prepared by using the wire material prepared by the present invention has good forming performance, no obvious macroscopic defects on the surface, uniform and fine structure, and mechanical properties reaching the level of ultra-high-strength aluminum alloy.
[0045] In summary, the present invention provides an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing, and a preparation method and application thereof. The wire is suitable for arc fuse additive manufacturing workpieces, has the characteristics of uniform and stable composition and smooth surface, and the additive workpieces have good formability, high surface quality, uniform microstructure and the ability to inhibit thermal cracks. The aluminum alloy additive manufacturing workpieces with high strength are finally obtained and can be widely used in the field of high-strength aluminum alloy arc fuse additive manufacturing.
[0046] The present invention provides an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing, and a preparation method and application thereof. The welding wire is filled with high-purity Mg wire to achieve high Mg content and low powder volume. The filling powder is composed of zirconium hydride, zirconium carbide, hexafluorozirconate and potassium fluoroaluminate, and is used to fill the gap between the Mg wire and the coating. The gas content in the powder is significantly reduced and the wire quality is improved. In the arc additive process, the design realizes fine grain strengthening and precipitation strengthening caused by high Zr content and precipitation strengthening caused by high Mg content, significantly improving the mechanical properties of the deposited material. The prepared welding wire has the characteristics of uniform composition, smooth surface and few impurities. The sample after additive has high strength and excellent comprehensive performance, can be widely used in aerospace, automobile manufacturing and other fields, and solves the problems of low strength and process defects of traditional aluminum alloy welding wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a microstructure diagram of the core-shell structure of ZrC and Al3Zr in the sample after the wire material obtained in Example 1 of the present invention is printed by the arc additive process; wherein the inner core of the core-shell structure is ZrC and the outer shell is Al3Zr;
[0048] Figure 2 This is a surface image of a sample in arc additive deposition state according to Example 1 of the present invention;
[0049] Figure 3 This is a microstructure diagram of the arc additive deposition sample in Example 1 of the present invention. DETAILED DESCRIPTION
[0050] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0051] Unless otherwise specified, the equipment, devices, materials, etc. used in the following examples are all obtained through conventional commercial channels or can be prepared by existing mature processes.
[0052] Example 1
[0053] The aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing prepared in this embodiment is selected as the O-state 1060 aluminum strip with a width of 7mm and a thickness of 0.8mm as the coating (the mass percentage of each element is: Si0.25wt%, Fe: 0.29wt%, Mn: 0.03wt%, and the balance is Al), and a high-purity Mg wire with a diameter of 1.1mm (purity greater than 99%) is selected. The filling ratio is 3.5wt%, and the mass percentage of the powder composition is: zirconium hydride (ZrH2) 60wt%, zirconium carbide (ZrC) 15wt%, lithium hexafluorozirconate 15wt%, and potassium fluoroaluminate (KAlF4) 10wt%.
[0054] A method for preparing an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing comprises the following steps:
[0055] S0: Aluminum strip (coating) processing and cleaning
[0056] Select 7mm wide and 0.8mm thick O-state 1060 aluminum strip as the coating. Use a scraper to mechanically clean the oxide layer and oil stains on the surface of the aluminum strip. Use anhydrous ethanol to wipe the surface of the aluminum strip to ensure that there is no residual material. Dry the cleaned aluminum strip in an 80℃ drying oven for 1 hour for later use.
[0057] S1: Preparation of drug powder and core material
[0058] Zirconium hydride, zirconium carbide, lithium hexafluorozirconate and potassium fluoroaluminate are mixed according to a proportion, the particle size of zirconium carbide is less than 50nm, preferably 40nm, and are evenly mixed using a ball mill. The particle size of other powders is controlled at 30-50μm, preferably 30μm.
[0059] Select high-purity Mg wire with a diameter of 1.1 mm, clean it and fix it to the wire feeding turntable.
[0060] S2: Core Wire Forming
[0061] The aluminum strip is bent into a "U"-shaped groove using a roller device for covering the core material.
[0062] The high-purity Mg wire and the top of the "U"-shaped aluminum strip are fixed and fed into the equipment simultaneously. The powder is evenly filled into the "U"-shaped groove through the filler, and the powder filling ratio is 3.5% of the wire quality. The aluminum strip is coated to form a round wire, and the wire is sealed and rolled using a roller device to ensure that the seam is tight and seamless.
[0063] S3: Wire post-processing
[0064] The wire was initially rolled to a diameter of 2 mm, and low speed (aluminum strip feed speed 20 m / min) and high pressure (1000 N / mm) rolling were used during the rolling process.
[0065] Then it was sent to a vacuum annealing furnace and kept at 300°C for 30 minutes to eliminate processing stress. The wire was gradually drawn to 1.3 mm using a continuous drawing device, and the cross-sectional diameter reduction was controlled at 15% each time.
[0066] The surface is polished to ensure that the wire surface is smooth and flawless, and finally it is rolled and vacuum packed for storage.
[0067] S4: Arc Additive Manufacturing
[0068] A 10 mm thick aluminum substrate was used as the deposition substrate, which was fixed on the positioner workbench after cleaning and drying. An ABB six-axis robot and a Fronius servo power supply were used, and the following welding parameters were set: current: 65 A, voltage automatic matching, welding gun moving speed: 24 mm / s, shielding gas was pure Ar, and the flow rate was 25 L / min.
[0069] The additive printing path adopts a single-pass mode, and multi-layer additive printing is performed according to the designed path. The preparation size is as follows: Figure 2 The cylindrical ring shown (height 95mm, circumference 684mm, hemisphere diameter 100mm).
[0070] S5: Additive Post-Processing
[0071] The additive plate was homogenized at 420°C for 12 hours and slowly cooled to room temperature. The sample after additive was sampled and the composition was tested using ICP-MS. The element mass percentages of the actual additive sample were: Mg: 8.83%, Mn: 0.04%, Zr: 1.13%, Fe: 0.31%, Si: 0.17%, and the rest were Al and unavoidable impurity elements.
[0072] The invention discloses an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing and its application in high-strength aluminum alloy arc fuse additive manufacturing.
[0073] High-strength aluminum alloy arc fuse additive is used in the demanding and high-performance fields of aerospace and high-end automobile manufacturing.
[0074] like Figure 1 As shown, it is a microstructure diagram of the core-shell structure of ZrC and Al3Zr in the sample after the wire material obtained in this embodiment is printed using the arc additive process; wherein the inner core of the core-shell structure is ZrC and the outer shell is Al3Zr.
[0075] like Figure 3 As shown, it is the microstructure diagram of the arc additive deposited sample of this embodiment. This embodiment realizes the fine grain strengthening and precipitation strengthening caused by high Zr content and the precipitation strengthening caused by high Mg content. The surface of the deposited layer is bright without obvious oxide inclusions, and the grain size is significantly refined (<10μm).
[0076] Comparative Example 1
[0077] S0: commercial 5183 finished wire with a wire diameter of 1.2 mm. The actual composition of the wire is as follows: Si: 0.4%, Fe: 0.12%, Mn: 0.40%, Mg: 5.8%, Al: balance;
[0078] S1: Aluminum alloy plate is used as the substrate, with a thickness of 10 mm, and the specific element mass percentages are: Si: 0.36%, Fe: 0.70%, Al: balance; the surface is polished with a sander to remove the surface oxide layer, cleaned and dried with alcohol, and sandblasted with 80-mesh sand in a sandblaster. After being taken out, it is cleaned and dried again with alcohol, and placed on the workbench of the arc fuse additive robot positioner;
[0079] S2: Using an ABB six-axis robot and a Fronius servo power supply, the current parameters were set to 70A, the voltage was automatically adjusted, the wire feeding speed was automatically matched, the welding gun forward speed was 24mm / s, the shielding gas was high-purity Ar, the shielding gas flow was 25L / min, and the program was set to the Fronius Al-5Mg professional program. Additive manufacturing was performed by multi-pass superposition, and the final size of the prepared sample was 94.3mm in height, 687mm in circumference, and 100.6mm in hemispherical diameter (the dimensional accuracy deviation was less than 1.1%).
[0080] S3: After the plate is cut, it is homogenized and heat treated at 450°C for 12 hours before being taken out for subsequent experiments.
[0081] The following experiments were performed to test the various properties of Example 1 and Comparative Example 1 of the present invention:
[0082] 1. Mechanical properties test
[0083] The transverse and longitudinal tensile properties of the heat-treated additive samples of Example 1 and Comparative Example 1 were tested using an electronic universal testing machine. The measured mechanical properties are shown in Table 1.
[0084] Table 1 Mechanical properties of Example 1 and Comparative Example 1
[0085]
[0086] The present invention develops an aluminum alloy wire suitable for high-strength aluminum alloy arc fuse additive and an application method thereof, which has the following advantages compared with the traditional aluminum alloy system:
[0087] The aluminum alloy wire prepared by the invention has the characteristics of uniform distribution of alloy elements and smooth and clean wire surface.
[0088] The samples prepared by using the wire material prepared by the invention have good forming properties, no obvious macroscopic defects on the surface, uniform and fine structure, and mechanical properties reaching the level of ultra-high-strength aluminum alloy.
[0089] In summary, the present invention provides a wire material that can be used for the preparation of arc fuse additive high-strength aluminum alloy workpieces and an application method thereof. The wire material is suitable for arc fuse additive manufacturing workpieces, has the characteristics of uniform and stable composition and smooth surface, and the additive workpiece has good formability, high surface quality, uniform microstructure and the ability to inhibit thermal cracks. The final high-strength aluminum alloy additive manufacturing workpiece can be widely used in the field of high-strength aluminum alloy arc fuse additive manufacturing.
[0090] Example 2
[0091] The difference between this embodiment and embodiment 1 is only that:
[0092] The aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing prepared in this embodiment is selected from an O-state 1060 aluminum strip with a width of 10 mm and a thickness of 1.0 mm as the flux coating, and a high-purity Mg wire with a diameter of 1.5 mm (purity greater than 99%) is selected. The powder filling ratio is 4wt%, and the powder composition mass percentage is: zirconium hydride (ZrH2) 50wt%, zirconium carbide (ZrC) 10wt%, potassium hexafluorozirconate 30wt%, potassium fluoroaluminate (KAlF4) 10wt%.
[0093] A method for preparing an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing comprises the following steps:
[0094] S0: Aluminum strip (coating) processing and cleaning
[0095] Select O-state 1060 aluminum strip with a width of 10mm and a thickness of 1.0mm as the coating. Use a scraper to mechanically clean the oxide layer and oil stains on the surface of the aluminum strip. Use acetone to wipe the surface of the aluminum strip to ensure that there is no residual material. Dry the cleaned aluminum strip in a drying oven at 100℃ for 1.5 hours for later use.
[0096] S1: Preparation of drug powder and core material
[0097] Zirconium hydride, zirconium carbide, potassium hexafluorozirconate and potassium fluoroaluminate are mixed according to a proportion, the particle size of zirconium carbide is less than 50nm, preferably 30nm, and are evenly mixed using a ball mill. The particle size of other powders is controlled at 30-50μm, preferably 50μm.
[0098] Select high-purity Mg wire with a diameter of 1.5 mm, clean it and fix it to the wire feeding turntable.
[0099] S2: Core Wire Forming
[0100] The aluminum strip is bent into a "U"-shaped groove using a roller device for covering the core material.
[0101] The high-purity Mg wire and the top of the "U"-shaped aluminum strip are fixed and fed into the equipment simultaneously. The powder is evenly filled into the "U"-shaped groove through the filler, and the powder filling ratio is 4% of the wire quality. The aluminum strip is coated to form a round wire, and the wire is sealed and rolled using a roller device to ensure that the seam is tight and seamless.
[0102] S3: Wire post-processing
[0103] The wire was initially rolled to a diameter of 3 mm, and low speed (aluminum strip feed speed 25 m / min) and high pressure (1200 N / mm) rolling were used during the rolling process.
[0104] Then it was sent to a vacuum annealing furnace and kept at 350°C for 60 minutes to eliminate processing stress. The wire was gradually drawn to 1.6 mm using a continuous drawing device, with each section reduction controlled at 20%.
[0105] The surface is polished to ensure that the wire surface is smooth and flawless, and finally it is rolled and vacuum packed for storage.
[0106] The element mass percentages of the actual additive sample obtained by the additive method of Example 1 in this embodiment are: Mg: 10.85%, Mn: 0.05%, Zr: 1.42%, Fe: 0.17%, Si: 0.21%, and the rest are Al and unavoidable impurity elements.
[0107] The high-strength aluminum alloy arc fuse additive obtained in this embodiment has a transverse tensile strength of 451 MPa, a transverse yield strength of 325 MPa, a transverse elongation at break of 19.4%, a longitudinal tensile strength of 462 MPa, a longitudinal yield strength of 313 MPa, and a longitudinal elongation at break of 16.7%.
[0108] Example 3
[0109] The difference between this embodiment and embodiment 1 is only that:
[0110] The aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing prepared in this embodiment uses an 8mm wide and 0.5mm thick O-state 1060 aluminum strip as the coating, and a 0.7mm diameter high-purity Mg wire (purity greater than 99%). The powder filling ratio is 3wt%, and the powder composition mass percentage is: zirconium hydride (ZrH2) 80wt%, zirconium carbide (ZrC) 10wt%, sodium hexafluorozirconate 5wt%, potassium fluoroaluminate (KAlF4) 5wt%.
[0111] A method for preparing an aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing comprises the following steps:
[0112] S0: Aluminum strip (coating) processing and cleaning
[0113] Select 8mm wide and 0.5mm thick O-state 1060 aluminum strip as the coating. Use a scraper to mechanically clean the oxide layer and oil stains on the surface of the aluminum strip. Use anhydrous ethanol to wipe the surface of the aluminum strip to ensure that there is no residual material. Dry the cleaned aluminum strip in a 90℃ drying oven for 1.2 hours for later use.
[0114] S1: Preparation of drug powder and core material
[0115] Zirconium hydride, zirconium carbide, sodium hexafluorozirconate and potassium fluoroaluminate are mixed according to a proportion, the particle size of zirconium carbide is less than 50nm, preferably 50nm, and are evenly mixed using a ball mill. The particle sizes of other powders are controlled at 30-50μm, preferably 40μm.
[0116] Select high-purity Mg wire with a diameter of 0.6 mm, clean it and fix it to the wire feeding turntable.
[0117] S2: Core Wire Forming
[0118] The aluminum strip is bent into a "U"-shaped groove using a roller device for covering the core material.
[0119] The high-purity Mg wire and the top of the "U"-shaped aluminum strip are fixed and fed into the equipment simultaneously. The powder is evenly filled into the "U"-shaped groove through the filler, and the powder filling ratio is 3% of the wire quality. The aluminum strip is wrapped to form a round wire, and the wire is sealed and rolled using a roller device to ensure that the seam is tight and seamless.
[0120] S3: Wire post-processing
[0121] The wire was initially rolled to a diameter of 2 mm, and low speed (aluminum strip feed speed 15 m / min) and high pressure (700 N / mm) rolling were used during the rolling process.
[0122] Then it was sent to a vacuum annealing furnace and kept at 300°C for 40 minutes to eliminate processing stress. The wire was gradually drawn to 1.2 mm using a continuous drawing device, and the cross-sectional diameter reduction was controlled at 10% each time.
[0123] The surface is polished to ensure that the wire surface is smooth and flawless, and finally it is rolled and vacuum packed for storage.
[0124] The element mass percentages of the actual additive sample obtained by the additive method of Example 1 in this embodiment are: Mg: 5.57%, Mn: 0.04%, Zr: 1.23%, Fe: 0.25%, Si: 0.18%, and the rest are Al and unavoidable impurity elements.
[0125] The high-strength aluminum alloy arc fuse additive obtained in this embodiment has a transverse tensile strength of 428 MPa, a transverse yield strength of 294 MPa, a transverse elongation at break of 22.5%, a longitudinal tensile strength of 424 MPa, a longitudinal yield strength of 285 MPa, and a longitudinal elongation at break of 21.6%.
[0126] Example 4
[0127] The difference between this embodiment and embodiment 1 is only that:
[0128] The powder composition weight percentage is: zirconium hydride (ZrH2) 50wt%, zirconium carbide (ZrC) 20wt%, sodium hexafluorozirconate 10wt%, potassium fluoroaluminate (KAlF4) 20wt%.
[0129] The element mass percentages of the actual additive sample obtained by the additive method of Example 1 in this embodiment are: Mg: 8.73%, Mn: 0.03%, Zr: 0.98%, Fe: 0.28%, Si: 0.16%, and the rest are Al and unavoidable impurity elements.
[0130] The high-strength aluminum alloy arc fuse additive obtained in this embodiment has a transverse tensile strength of 457 MPa, a transverse yield strength of 313 MPa, a transverse elongation at break of 20.9%, a longitudinal tensile strength of 442 MPa, a longitudinal yield strength of 309 MPa, and a longitudinal elongation at break of 19.3%.
[0131] Comparative Example 2
[0132] The difference between this comparative example and Example 1 is only that:
[0133] Lithium hexafluorozirconate was replaced with zirconium fluoride ZrF4. After replacement, the core-shell structure of ZrC and Al3Zr was not found in the samples printed by arc additive process; the grain size was significantly increased (greater than 30μm), and the mechanical properties of the deposited material were significantly reduced. The arc fuse additive obtained in comparative example 2 had a transverse tensile strength of 369MPa, a transverse yield strength of 261MPa, a transverse elongation at break of 23.4%, a longitudinal tensile strength of 330MPa, a longitudinal yield strength of 245MPa, and a longitudinal elongation at break of 22.1%.
[0134] The element mass percentages of the arc fuse additive obtained in this comparative example are: Mg: 8.66%, Mn: 0.05%, Zr: 1.15%, Fe: 0.29%, Si: 0.12%, and the rest are Al and unavoidable impurity elements.
[0135] Comparative Example 3
[0136] The difference between this comparative example and Example 1 is only that:
[0137] The composition weight percentage of the powder is: zirconium hydride (ZrH2) 50wt%, zirconium carbide (ZrC) 5wt%, lithium hexafluorozirconate 35wt%, potassium fluoroaluminate (KAlF4) 10wt%.
[0138] In this comparative example, the core-shell structure of ZrC and Al3Zr was not found in the samples printed by arc additive process; the grain size was significantly increased (greater than 30μm), and the mechanical properties of the deposited material were significantly reduced. The arc fuse additive obtained in comparative example 2 had a transverse tensile strength of 352MPa, a transverse yield strength of 245MPa, a transverse elongation at break of 17.8%, a longitudinal tensile strength of 315MPa, a longitudinal yield strength of 223MPa, and a longitudinal elongation at break of 16.9%.
[0139] The element mass percentages of the arc fuse additive obtained in this comparative example are: Mg: 8.48%, Mn: 0.05%, Zr: 0.83%, Fe: 0.34%, Si: 0.19%, and the rest are Al and unavoidable impurity elements.
[0140] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.
[0141] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0142] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An aluminum alloy cored wire suitable for arc fuse additive manufacturing, characterized in that: Aluminum strip is used as the coating, and high-purity Mg wire and powder are used for filling; The drug powder accounts for 3-4% of the total mass of the wire; The medicine powder comprises the following components in percentage by mass: 50-80% of zirconium hydride, 10-20% of zirconium carbide, 5-30% of hexafluorozirconate and 5-20% of potassium fluoroaluminate.
2. The aluminum alloy cored wire suitable for arc fuse additive manufacturing according to claim 1, characterized in that: The hexafluorozirconate includes one or more of sodium hexafluorozirconate, potassium hexafluorozirconate, and lithium hexafluorozirconate.
3. The aluminum alloy cored wire suitable for arc fuse additive manufacturing according to claim 1, characterized in that: The particle size of zirconium carbide is less than 50 nm, and zirconium hydride, hexafluorozirconate and potassium fluoroaluminate are vacuum ball-milled to a particle size of 30-50 μm; The aluminum strip is an O-state 1060 aluminum strip with a width of 7-10 mm and a thickness of 0.5-1.0 mm; The diameter of high purity Mg wire is 0.7-1.5mm.
4. A method for preparing an aluminum alloy cored wire suitable for arc fuse additive manufacturing according to any one of claims 1 to 3, characterized in that: The following steps are involved: S0, skin treatment and cleaning; S1, Preparation of drug powder and core material: Zirconium hydride, zirconium carbide, lithium hexafluorozirconate and potassium fluoroaluminate are mixed according to the proportions. Clean and fix the high-purity Mg wire to the wire feeding turntable; S2, cored wire forming: Use roller equipment to bend the coating into a U-shaped groove to obtain a U-shaped aluminum strip. The high-purity Mg wire and the top of the U-shaped aluminum strip are fixed and fed into the equipment simultaneously. The powder is evenly filled into the U-shaped groove through the filler, and the U-shaped aluminum strip is coated to form a round wire. The wire is sealed and rolled using a roller device. S3, wire post-processing The wire is initially rolled to a diameter of 2-3 mm, with low speed and high pressure rolling. Then it is sent to a vacuum annealing furnace and kept at 300-350℃ for 30-60 minutes; then the wire is gradually drawn to 1.2-1.6mm using a continuous drawing device, and the cross-sectional diameter reduction is controlled at 10%-20% each time; The surface is then polished, rolled and vacuum packed for storage.
5. The preparation method according to claim 4, characterized in that: In S0, the method for treating and cleaning the coating is as follows: use a scraper to mechanically clean the oxide layer and oil stains on the surface of the coating; use anhydrous ethanol or acetone to wipe the surface of the coating to ensure that there is no residual substance, and dry the cleaned coating in a drying oven at 80-100℃ for at least 1 hour for use.
6. The preparation method according to claim 4, characterized in that: In S3, the low speed in the low-speed and high-pressure rolling is an aluminum strip feed speed of 15-25 m / min, and the high pressure is 700-1200 N / mm.
7. Use of the aluminum alloy flux-cored wire suitable for arc fuse additive manufacturing according to any one of claims 1 to 3 in high-strength aluminum alloy arc fuse additive manufacturing.
8. The use according to claim 7, characterized in that: The preparation method of high-strength aluminum alloy arc fuse additive is: S01, Arc Additive Manufacturing: Aluminum substrate was used as the deposition substrate, which was fixed on the positioner workbench after cleaning and drying. ABB six-axis robot and Fronius servo power supply were used, and the following welding parameters were set: current: 65A, voltage automatic matching, welding gun moving speed: 24mm / s, shielding gas was pure Ar, flow rate 25L / min; S02, Additive Post-Processing: The additive material was homogenized at 420°C for 12 hours and then slowly cooled to room temperature to obtain a high-strength aluminum alloy arc fuse additive material.
9. The use according to claim 8, characterized in that: The high-strength aluminum alloy arc fuse additive has a transverse tensile strength of 428-457MPa, a transverse yield strength of 294-325MPa, a transverse elongation at break of 19.4-22.5%, a longitudinal tensile strength of 424-462MPa, a longitudinal yield strength of 285-313MPa, and a longitudinal elongation at break of 16.7-21.6%.
10. The use according to claim 7, characterized in that: High-strength aluminum alloy arc fuse additive is used in the demanding and high-performance fields of aerospace and high-end automobile manufacturing.
Citation Information
Patent Citations
Flux cored wire, and production method and application thereof
CN105880867A
Micro-nano particle reinforced aluminum alloy core filler wire for welding 7075 aluminum alloy
CN110560957A
Micro-nano particle reinforced aluminum alloy flux-cored filler wire used for TIG welding of 7075 aluminum alloy
CN111015012A
Aluminum alloy flux-cored wire and preparation method thereof
CN113579556A
Stranded wire welding wire capable of inhibiting solidification cracks of high-strength aluminum alloy and preparation method of stranded wire welding wire
CN116160150A